1983
DOI: 10.1126/science.6308763
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression in Escherichia coli of Enzymatically Active Harvey Murine Sarcoma Virus p21 ras Protein

Abstract: The gene for the Harvey murine sarcoma virus (Ha-MuSV) p21ras protein was fused to the amino-terminal portion of the bacteriophage lambda cII gene on the expression vector pJL6. The fusion was such that transcription was controlled by the well-regulated phage lambda pL promoter, and translation initiated in the cII gene continued in frame into the ras gene sequences that code for p21. When the pL promoter was derepressed, the Escherichia coli cells harboring the fusion plasmid synthesized 23,000-dalton protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 15 publications
0
25
1
Order By: Relevance
“…E. coli carrying plasmid pJLcIIrasI was grown in a fermentor (14). All p21 purification procedures were performed at 0 to 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli carrying plasmid pJLcIIrasI was grown in a fermentor (14). All p21 purification procedures were performed at 0 to 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrate that p21 possesses three distinctive activities, i.e., GTP/GDP binding, autokinase, and GTPase, which are also detectable in p21 overproduced in microorganisms (13,14,21,22,28,30,32). Importantly, the p21 proteins ofactivated oncogenes have reduced GTPase activities compared with those of proto-oncogenes (10, 17, * Corresponding author.…”
mentioning
confidence: 99%
“…DNA transfection studies utilizing the molecularly cloned proviral DNA of Ha-MuSV and studies on the thermolability of the p21 protein of a temperature-sensitive mutant of Ki-MuSV have concluded that the p21 proteins are the gene products mediating the virusinduced malignant transformation of normal cells (4,6,20,25). p21 proteins of Ha-MuSV and Ki-MuSV possess a guanine nucleotide-binding activity and an autophosphorylation activity at the 59th threonine residue (8,9,(14)(15)(16). In contrast to the viral p21 protein, the cellular homologs are not phosphorylated due to substitution for the threonine residue with an alanine residue at the major phosphorylation site.…”
mentioning
confidence: 99%
“…Mutant p2l clones were inserted into the bacterial expression vector pJL6 (17), and the proteins were purified as described previously (5). As controls, mutant proteins altering amino acid 12 or amino acid 59 or both were included.…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of bacterially expressed mutant p2ls, the 0.88-kilobase Hindlll fragment from each mutant pSV2neo/ras clone was purified and ligated into the Hindlll site of the plasmid vector pJL6 (17 (5).…”
Section: Methodsmentioning
confidence: 99%